(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
With the development of technology that is increasingly becoming a challenge for education in today’s digital era, educators or teachers and students or students in this era must be able to communicate and adapt to the times, in terms of technological developments, it must be directly proportional to the mastery of competencies that require completion. problems with high thinking. With the Corona Virus Disease 19 (Covid-19) pandemic, the government through the Minister of Education and Culture of the Republic of Indonesia issued two policies through Circular Letter No. 3 of 2020. Along with the development of Information and Technology as well as the internet network, learning can be done online. So many terms such as e-learning emerged, namely learning using electronic devices. more than 2 years of learning using online technology, both teachers and students who are used to using hardware and software technology. In the even semester of the academic year, the new school policy is allowed to conduct face-toface learning with very strict health protocols. based on online learning experience, teachers still use Software that has been provided by the Ministry of Education and Culture, Research, Technology and Higher Education, namely Belajar.id, especially at SMP Negeri 15 Surakarta where there is a Form menu that can be used to make test questions starting from making daily questions, UTS and UAS on the grounds that they do not have to be in the form of print a lot and can take advantage of Computer Laboratory facilities that can be used to make assessments to students or learners. Based